2022
DOI: 10.1002/oby.23316
|View full text |Cite
|
Sign up to set email alerts
|

National childhood obesity‐related intervention systems and intervention programs in China in 1949 to 2020: A narrative review

Abstract: Objective This review examines main government and nongovernmental institutions for childhood obesity prevention and control in China, as well as major national interventions for childhood obesity. Methods PubMed, China National Knowledge Infrastructure (CNKI), Wanfang, official websites of national governments and professional institutions/associations, Baidu.com, and Google.com were systematically searched in March 2020 to April 2020. A total of 20 international and national experts on childhood obesity were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…To improve the health of poor rural students, the state launched the "Nutrition improvement program for rural compulsory education students" in 2011, with the financial department providing nutritional meal subsidies for rural compulsory education students (approximately 7-15 years) in poor areas of central and western areas. In the beginning, each student was provided with a subsidy of 3 yuan per study day, which was increased to 4 yuan in 2014 and 5 yuan in 2021, and the subsidy amounted to 34.8 billion yuan in 2021 74,75 . Through this, the average height and weight of students increased, and the gap between urban and rural areas narrowed; micronutrient deficiencies such as anemia decreased; the intake of foods rich in high-quality protein and micronutrients such as fish, poultry, meat, eggs and milk increased, and rural students' nutrition levels improved 74,75 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the health of poor rural students, the state launched the "Nutrition improvement program for rural compulsory education students" in 2011, with the financial department providing nutritional meal subsidies for rural compulsory education students (approximately 7-15 years) in poor areas of central and western areas. In the beginning, each student was provided with a subsidy of 3 yuan per study day, which was increased to 4 yuan in 2014 and 5 yuan in 2021, and the subsidy amounted to 34.8 billion yuan in 2021 74,75 . Through this, the average height and weight of students increased, and the gap between urban and rural areas narrowed; micronutrient deficiencies such as anemia decreased; the intake of foods rich in high-quality protein and micronutrients such as fish, poultry, meat, eggs and milk increased, and rural students' nutrition levels improved 74,75 .…”
Section: Discussionmentioning
confidence: 99%
“…In the beginning, each student was provided with a subsidy of 3 yuan per study day, which was increased to 4 yuan in 2014 and 5 yuan in 2021, and the subsidy amounted to 34.8 billion yuan in 2021 74,75 . Through this, the average height and weight of students increased, and the gap between urban and rural areas narrowed; micronutrient deficiencies such as anemia decreased; the intake of foods rich in high-quality protein and micronutrients such as fish, poultry, meat, eggs and milk increased, and rural students' nutrition levels improved 74,75 . A study from CNSSCH found an increase in the percentage of children and adolescents meeting one hour of in-school physical activity 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, the prevalence of stunting in urban children and adolescents in China decreased from 8.6% to 1.4% between 1985 and 2014, while it decreased from 24.2% to 3.2% in rural areas (Song et al, 2019). During this period, the Chinese government noted serious nutritional deficiencies in rural areas, and to improve the growth and development of rural children, the state launched the “Nutritional Improvement Program for Rural Compulsory Education Students” in 2011 (Li, Taerken, et al, 2023; Ma et al, 2022). Through this initiative, rural children's diets have changed and their nutritional levels have improved, contributing to an increase in adult height.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, these interventions focused on school-based nutrition and physical activity programs. 5 For example, in 2008, the Bureau of Disease Prevention and Control National Health Commission revised the Guidelines for the Prevention and Control of Overweight and Obesity Among School Aged Children and Adolescents in China. 5 Infant nutrition has also been a focus with nutrition assessment and dietary guidance before and during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“… 5 For example, in 2008, the Bureau of Disease Prevention and Control National Health Commission revised the Guidelines for the Prevention and Control of Overweight and Obesity Among School Aged Children and Adolescents in China. 5 Infant nutrition has also been a focus with nutrition assessment and dietary guidance before and during pregnancy. While not initially implemented as an obesity control and prevention policy, in the 1990s China began implementing the ‘Baby-friendly hospital initiative’ (BFHI) to promote exclusive breastfeeding, which is now known to reduce the risk of OAO later in life as is considered by nutrition researchers as a ‘double-duty’ intervention.…”
Section: Introductionmentioning
confidence: 99%